Analysis of the phenomenon of violence in a family based on a questionnaire carried out among students - Waksmańska, Wioletta; Grzywna, Teresa; Łukasik, Renata (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. The phenomenon of violence in a family is one of the greatest risks of modern civilisation. Many parents fail to carry out their care and educational functions and, through applying violence against children, they pass the pathologic models of behaviour. Aim. The objective of the carried out research has been to determine what forms of violence are most commonly applied by parents against their children, and which of the parents applies the violence more frequently. Material and methods. The analysis was made based on anonymous questionnaires. The questionnaires referred to 60 children at the age from 10 to 18 years. Results and conclusions. As a result of the analysis, it has been concluded that the most common acts of violence applied by parents against their children are yanking, beating and calling names. This is done both by mothers and fathers. In most cases, children do not report to anybody that they are victims of violence in their families.